IMPROVEMENT OF THE TRAINING PROCESS ON PREVENTION AND ELIMINATION OF EMERGENCY SITUATIONS IN EDUCATIONAL INSTITUTIONS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article proposes a comprehensive approach to improving the educational process of emergency prevention and response in educational institutions. It discusses the importance of proactive measures, analyzes the existing literature on teaching methods, presents effective teaching methods, and provides recommendations for implementation.